THE ROLE OF MOBILING TEACHERS IN TEACHNG ENGLISH AT SECONDARY SCHOOL - Mala Tundu, Ika Riana; Panggua, Selvi; Mangoki, Dan (Publikasi dan UKI Press UKI Toraja., 2024)
The purpose of this study is to find out their experience in implementing their role in teaching English at Secondary school. In this study, researchers used qualitative methods. Respondents in this study consisted of 2 mobilizing teachers of English. The study was collected based on interviews and documentation. Then analyzed through data collection, data reduction, data presentation and conclusion. The results of this study show the mobilizing teachers in carrying out their role in teaching English in secondary schools is as follow: be a learning leader, coach for other teacher, agents of change, learner-oriented leader, innovation and creativity, inspire and motivate students, as well as in implementing the role as a mobilizing teachers, each has its own way.